Good work through decent work: Practices of sixteen unionized firms in the Philippines - Edralin, Divina M. (Animo Repository, 2016)
This paper aims to describe the good work, through the decent work practices of 16 unionized firms, in the hotel, banking, airline, and broadcast industries in the Philippines, as stipulated in their Collective Bargaining Agreements (CBAs), and based on five Decent Work Agenda dimensions. This study is primarily founded on the Social Doctrine of the Church on Human Work; the ILO’s Decent Work Agenda as incorporated in Ghai’s (2006) model; and the theory of Collective Bargaining of Edralin (2003). Results showed that there are many good work, through decent work practices of unionized firms, in the aspects of opportunities for work, productive work, equity in work, security at work, and representation at work, as provided in their CBAs. Findings also revealed that collective bargaining is a powerful vehicle that can help ensure that the implementation of the five dimensions of decent work in the workplace can lead to the securing of just wages, strengthening of unions, inclusion of the poor working people in society, and workers having a chance to a life of human dignity. A union is strong primarily because of its membership’s solidarity, vigilance, and capacity to mobilize, which together with the protection afforded by legislation to workers, help persuade, if not pressure employers to manage their firms diligently and in good faith. At the policy level, it is recommend that the labor relations framework currently used by the DOLE be amended to more effectively implement decent work practices and promote collective bargaining. © 2016 by De La Salle University.